MyDispense workshop: integration of virtual simulation in teaching and learning activity / Farhana Fakhira Ismail and Assoc. Prof. Dr. Mahmathi Karuppannan - Ismail, Farhana Fakhira; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
MyDispense is an online pharmacy simulation platform developed by Monash University that allows students to practice their dispensing skills. It provides a secure environment where students are able to practice skills and build confidence while learning from mistakes, if any, without severe consequences before practicing in the real world. From initial communication with the patient and prescriber to professional advice when handing medicines to patients, the web application supports the entire dispensing experience. It can be used as either clinical/hospital or community pharmacy settings.